Cherokee Meadows Road Association - State Fire Assistance - Colorado State Forest Service, compiler (Colorado State University. Libraries, 2011)
Located in: Fort Collins office files. Cherokee Meadows Road Association (CMRA) records related to their Colorado State Forest Service (CSFS) State Fire Assistance (SFA) and Colorado Wildland Urban Interface (WUI) grant programs. Includes: WUI grant application; program payment and reimbursement requests; reimbursement calculation worksheets; cost documentation; financial spreadsheets; invoices; receipts; scope of work and accomplishment reports; CMRA annual meeting minutes; notes; CSFS publication order form; printout of CMRA and firewise.org webpages with annotations; and annotated maps.
Keywords: Colorado State Forest Service -- History -- Sources; Forests and forestry--Colorado